2022
DOI: 10.1227/neu.0000000000002212
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Very Small Aneurysm Size and Anterior Communicating Segment Location on Outcome after Aneurysmal Subarachnoid Hemorrhage

Abstract: BACKGROUND:Very small anterior communicating artery aneurysms (vsACoA) of <5 mm in size are detected in a considerable number of patients with aneurysmal subarachnoid hemorrhage (aSAH). Single-center studies report that vsACoA harbor particular risks when treated.OBJECTIVE:To assess the clinical and radiological outcome(s) of patients with aSAH diagnosed with vsACoA after aneurysm treatment and at discharge.METHODS:Information on n = 1868 patients was collected in the Swiss Subarachnoid Hemorrhage Outcome Stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…2-4 On contrary, other authors concluded that aneurysms located in the anterior communicating complex are among those with the highest risk of rupture. 3-6 Authors 1 of this study reported that aneurysms smaller <5 mm comprised 12% of all ruptured and 33% of all ruptured anterior communicating artery (AcoA) aneurysms, congruent with the findings of previous studies. 4,5,7 Although not as significant as the findings by Waqas et al, 8 who reported 6-mm mean size of rupture aneurysms in the anterior circulation; it nevertheless reopens the known dilemma when counseling patients harboring innocent small AcoA aneurysm.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…2-4 On contrary, other authors concluded that aneurysms located in the anterior communicating complex are among those with the highest risk of rupture. 3-6 Authors 1 of this study reported that aneurysms smaller <5 mm comprised 12% of all ruptured and 33% of all ruptured anterior communicating artery (AcoA) aneurysms, congruent with the findings of previous studies. 4,5,7 Although not as significant as the findings by Waqas et al, 8 who reported 6-mm mean size of rupture aneurysms in the anterior circulation; it nevertheless reopens the known dilemma when counseling patients harboring innocent small AcoA aneurysm.…”
supporting
confidence: 90%
“…In conclusion, we congratulate Roethlisberger et al 1 for providing a unique insight into the characteristics of virtually all ruptured aneurysms treated in Switzerland, further emphasizing the dangerous nature of very small aneurysms of the anterior communicating complex.…”
mentioning
confidence: 81%
See 3 more Smart Citations